MAKNA FILOSOFIS BANGUNAN KRATON SURAKARTA - - Purwadi (JURNAL IKADBUDI, 2013)
This article will describe about symbolic meaning and phylosophy value in Kraton Surakarta.In 1745 Sunan Paku Buwono II moved his court to nearby Surakarta where he had built a new palace. When the king ordered to move the capital city of Kartasura eastward to the banks of Javas longest river, it was certainly not without reasons. At that time over land communication was scarce because of inaccesible swamps, high mountain ranges and impenetrable forests. But the city must have its outlet, its contact with outer islands and Bengawan then was the only economic and social life line. Keyword: Kraton Surakarta, phylosophy, symbolic